Correlations between Three Patient-Assessed Shoulder Instability Scales. (August 2015) - Taylor, David; Garewal, Devinder; Evans, Matthew C
Purpose: To evaluate the correlations between three patient-assessed shoulder instability scales before and after Latarjet stabilisation for traumatic antero-inferior glenohumeral instability. Methods: Records of 30 men and 2 women (mean age, 26.7 years) who had not undergone surgery for antero-inferior shoulder instability and records of 31 men and one woman (mean age, 27 years) who had undergone Latarjet stabilisation for antero-inferior shoulder instability and had been followed up for a mean period of 21.3 months were reviewed. Correlations between the Western Ontario Shoulder Instability Index (WOSI), the Melbourne Instability Shoulder Score (MISS), and the L'Insalata Shoulder Questionnaire (L'Insalata) were assessed. Results: The mean score of each scale was significantly greater in the postoperative than preoperative group (p<0.001). Within each group, the mean scores of the 3 scales differed significantly (ANOVA, p=0.001). The mean L'Insalata score was significantly higher than the mean WOSI and MISS scores (p<0.01, post-hoc analysis), but the latter 2 scores did not differ significantly (p>0.01, post-hoc analysis). Correlations of all scale pairs were significant (p<0.001). The WOSI-MISS correlations in the pre- and post-operative groups were moderate. The L'Insalata-WOSI correlations in the pre- and post-operative groups were moderate and high, respectively. The L'Insalata-MISS correlations in the pre- and post-operative groups were high and moderate, respectively. Conclusion: The MISS and WOSI scales are moderately correlated. Correlation of the L'Insalata scale with other scales depends on the operative status of the patient. The use of the L'Insalata scale alone is not recommended.